Bibliometric analysis and systematic literature review of the relationship between sustainable development goals and sustainable entrepreneurship over time - Elba Patricia Benavides-Sánchez; Ismael Moya-Clemente; Gabriela Ribes-Giner (Discover Sustainability)
Abstract Sustainable entrepreneurship (SE) has proven to be the key to achieving the 17 Sustainable Development Goals (SDGs), because of its ability to identify opportunities and foster innovations. The vision of SE is global, inclusive and supportive addressing environmental challenges, social inequalities and economic insecurity. Therefore, researchers and scholars have conducted previous studies on the SE in the SDGs, but there are still gaps in the research, such as a study that presents a detailed and updated picture of their relationship in specific contexts. This study therefore takes an innovative approach and explores the relationship between SE and SDGs. Through a bibliometric analysis of academic publications registered in Scopus, thematic trends, author collaborations and leading research countries were analyzed, in addition to conducting a comprehensive systematic literature review answering research question How can contribute to the 5 SDGs axes? The study identified the “give-receive-return” relationship, which we call the SE value cycle, a conceptual tool that helps to understand the interaction between innovation with the market, operation and the 5 axes of the 2030 Agenda. This finding opens up significant new opportunities for future research, with important implications for policymakers, business, academia and society, who seek to promote a more just, prosperous and sustainable world for those of us here, as well as for future generations.